2019
DOI: 10.1038/s41401-019-0300-2
|View full text |Cite
|
Sign up to set email alerts
|

Icariside II inhibits lipopolysaccharide-induced inflammation and amyloid production in rat astrocytes by regulating IKK/IκB/NF-κB/BACE1 signaling pathway

Abstract: β-amyloid (Aβ) is one of the inducing factors of astrocytes activation and neuroinflammation, and it is also a crucial factor for the development of Alzheimer’s disease (AD). Icariside II (ICS II) is an active component isolated from a traditional Chinese herb Epimedium , which has shown to attnuate lipopolysaccharide (LPS)-induced neuroinflammation through regulation of NF-κB signaling pathway. In this study we investigated the effects of ICS II on LPS-induced astrocytes activation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 59 publications
1
25
0
Order By: Relevance
“…For instance, βArr2 inhibited the pro-inflammatory cytokines TNF-α and IL-6 and activation of transcription factor NF-κB, increased the expression of anti-inflammatory cytokines IL-10 and IL-4 in microglia for enhancing neurological function in encephalitis mice [ 31 ]. Consistent with prior studies, the activation of the NF-κB pathway played a critical part in inflammatory disorders, and the p50/p65 heterodimer was the most common form of NF-κB activation [ 32 ]. NF-κB could bind to the inhibitor IκB in cytoplasm, resulting in inactivated.…”
Section: Discussionsupporting
confidence: 82%
“…For instance, βArr2 inhibited the pro-inflammatory cytokines TNF-α and IL-6 and activation of transcription factor NF-κB, increased the expression of anti-inflammatory cytokines IL-10 and IL-4 in microglia for enhancing neurological function in encephalitis mice [ 31 ]. Consistent with prior studies, the activation of the NF-κB pathway played a critical part in inflammatory disorders, and the p50/p65 heterodimer was the most common form of NF-κB activation [ 32 ]. NF-κB could bind to the inhibitor IκB in cytoplasm, resulting in inactivated.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, NF‐κB regulates the expression of about 500 different genes, including iNOS and COX‐2 76 . Furthermore, inflammatory mediators and NF‐κB interact, such as the activation of NF‐κB signaling pathways by IL‐1β, TNF‐α, and iNOS, leading to aggravated neuroinflammation 77 . To further clarify the in‐depth mechanisms of PSO in inhibiting neuroinflammation, we explored PSO's effects on the NF‐κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has suggested that ICAII may serve a beneficial impact in various types of disease, such as Alzheimer's disease, osteoporosis, stroke, breast cancer and leukemia, possibly due to its multiple bioactivities, including antioxidative, anti-inflammatory and anti-apoptotic properties (19). Recent studies have reported that ICAII may also be beneficial for cardiovascular disease; for example, Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has suggested that ICAII may serve a beneficial impact in various types of disease, such as Alzheimer's disease, osteoporosis, stroke, breast cancer and leukemia, possibly due to its multiple bioactivities, including antioxidative, anti-inflammatory and anti-apoptotic properties ( 19 ). Recent studies have reported that ICAII may also be beneficial for cardiovascular disease; for example, in a rat model of spontaneous hypertension, Wu et al ( 13 ) demonstrated that the intra-gastric administration of ICAII (4, 8 or 16 mg/kg) significantly decreased the blood pressure, promoted heart functional recovery and improved ventricular remodeling.…”
Section: Discussionmentioning
confidence: 99%